EVALUASI PERSIAPAN MENGAJAR GURU EKONOMI BERDASARKAN KURIKULUM 2013 DI SMA NEGERI SE-OGAN ILIR - Ali Barka; Yulia Djahir; Ikbal Barlian (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2015)
This study aims to Know Teachers’ teaching Preparation Teaching Economics in Implementing Curriculum 2013 at SMA Negeri in the district Ogan Ilir, correlating to the preparation in the form of an annual program, the semester program, Syllabus, RPP (Lesson Plan), media / props, LKS (Student Worksheet), Task Sheet, Sheets of research, and Textbook prepared by the Economics teachers in the district of Ogan Ilir on the basis of the 2013 curriculum. This study is a qualitative research, and the data collection techniques used here is In the form of interview techniques and documentation. Interview data is used to determine the ability of teachers to understand the preparations made in accordance with the 2013 curriculum. Interviews were conducted in three meetings on economics teachers at SMA in the district of Ogan Ilir and documentation of data is used to support the interview data. Overall, Data on the interview show that the result is "good", while the data showing the result of the documentation 88% put into good category. The conclusions of this study evaluation of teaching economics teacher preparation curriculum by 2013 has been classified as "good ". There is also the suggestion from this study teachers are expected to prepare more mature again on the provision of technology-based media and textbooks and improving competence in curriculum implementation in 2013 for the purpose of education can be achieved and the support by the Government in this case the local education office at Ogan Ilir can be the facilitate the application of 2013 curriculum at SMA of Ogan Ilir district and has a program that can support in achieving the educational goals.